Mapping the Role of Social Media Marketing in Purchase Decisions through Brand Trust: A Systematic Review and Bibliometric Analysis - Titisari Ambarwati; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
The rapid development of digital technologies has significantly transformed marketing practices and consumer behavior. In recent years, digital marketing, particularly through social media platforms, has become an essential strategy for firms to enhance consumer engagement and influence purchase decisions. Despite the growing body of literature, the relationships among social media marketing, brand trust, customer preference, and purchase decision remain fragmented across previous studies. Therefore, this study aims to provide a comprehensive overview of the research landscape and identify emerging trends in this field. This study employs a Systematic Literature Review (SLR) combined with bibliometric analysis to examine publications related to social media marketing, brand trust, customer preference, and purchase decision. Data were collected from the Scopus database covering the period from 2021 to 2026. Bibliometric mapping and keyword co-occurrence analysis were conducted using VOSviewer to identify research clusters, thematic structures, and the evolution of research topics. The findings reveal a significant increase in publications on social media marketing and consumer behavior, indicating growing academic interest in this domain. The bibliometric analysis shows that social media marketing acts as a central theme connecting key variables such as brand trust, customer preference, and purchase intention/decision. Furthermore, overlay visualization indicates that emerging research topics include consumer engagement, influencer marketing, electronic word-of-mouth (e-WOM), and perceived value, reflecting a shift toward a more integrated and experiential understanding of consumer behavior in digital environments. This study contributes to the literature by mapping the intellectual structure and research evolution in the social media marketing domain and highlighting potential directions for future research. The findings also provide insights for researchers and practitioners in developing more effective and trust-oriented digital marketing strategies to influence consumer purchase decisions